Multimedia Pembelajaran Sistem Pernafasan Pada Manusia Di Sekolah Dasar Negeri 09 Kota Pagar Alam Menggunakan Adobe Animate - S. Prawira, Nanda (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
This take a look at aimed to apply multimedia studying approximately the human respiratory device at Public primary college 09 in Pagar Alam town and decorate gaining knowledge of interest and overall performance.This studies is based on less effective and much less thrilling techniques.The development technique used is ADDIE (analysis, design, development, Implementation, assessment).The equipment used for multimedia learning improvement fashions are Adobe Animate. Primarily based on the outcomes of the professional evaluation done, the average value is 4.2 with a very legitimate category.Then, primarily based at the outcomes of the sector check or alpha and beta trying out received from the pre- and submit-check consequences, the average pupil scored 8.7 factors inside the good class so the N-Gain value is 0.8 for the good category high.This showed an growth in getting to know results earlier than and after the usage of multimedia gaining knowledge of about the human respiration system